Le développement durable : thématique nouvelle, rhétorique conventionnelle - Philippe Genestier; Claudine Jacquenod-Desforges (Territoire en Mouvement)
Speeches about sustainable development represent an opportunity for political leaders to mobilize wide audiences, as they refer to crucial worldwide issues. The discursive analysis of seventy-four cases, however, sheds light on a common feature: the speakers characteristically hesitate between personal commitment and self-effacement. We argue that the theme of sustainable development -both flourishing and self-contradictory- forcefully drives the speaker to alternate between authoritarian, scientific and conciliatory perspectives. It may thus appear much less fruitful than it is usually recognized.